Teachers' Perception on Integrating Technology In Differentiated Instruction and Collaborative Learning: A Case Study - Mustofa, Mustofa (Jurnal Simki Pedagogia, 2024)
The purpose of this case study is to explore the percepation of Taiwanese middle school teachers on the implementation of digital technology in order to facilitate differentiated instructions and collaborative learning, ultimately enhancing the effectiveness and equity of learning environments in diverse classrooms. The researcher performed observations and semi-structured interviews with three proficient teachers with experience utilizing technology. The results demonstrate that teachers recognize ample potential and prospects in employing digital technology to tailor teaching methods and foster an equitable and supportive learning atmosphere.